Effect of exergaming-based balance training on short term memory and spatial cognition in healthy young adults: a randomized controlled trial - Sadawarte, Sneha S.; Pazare, Shamla W. (International Journal Of Community Medicine And Public Health, 2025)
Background: Physical exercises are crucial in cognitive functioning. Centres in brain responsible for balance function coincide with cognitive functions centres like short term memory and spatial cognition. Young population faces immense stress which causes cognitive deterioration. Conventional balance training has shown to have positive impact on cognitive functioning. Exergaming is a relatively new frontier which creates interest among young adults. Researchers speculated that stimulating the vestibular system during the training induces the changes of the hippocampus and the parietal cortex. Methods: Seventy healthy young individuals participated. Participants were selected using inclusion and exclusion criterion and randomly divided in two equal groups using computerized randomization. Group A and Group B had Conventional and Exergaming based balance training protocol respectively, thrice a week for six weeks. Backward digit span test and perspective taking/ spatial orientation test (PTSOT) was used to assess pre and post intervention short term memory and spatial cognition respectively. Statistical analysis and conclusion were drawn. Results: Both groups had statistically significant improvement in post intervention backward digit span scores (p value=0.000 in each). Although, no significant difference was observed between the groups. Similarly, both groups had statistically significant improvement in post intervention PTSOT (p value <0.0001 in Group A and p value 0.0006 in Group B). Although, no significant difference was observed between the groups. Conclusions: Conventional and exergaming-based balance exercises are equally effective in healthy young individuals to improve spatial cognition.